Intensive parenting, guilt, shame, and psychological well-being of stay-at-home mothers in Pakistan: a cross-sectional survey - Qayyum, Laiba; Javed, Aiman; Zafar, Muhammad Shoaib; Gul, Mirrat (Journal of the Pakistan Medical Association, 2026)
Objective: To explore the prevalence of intensive parenting attitudes among stay-at-home mothers, the relationship between such attitudes and psychological wellbeing, and the mediating role of guilt and shame between intensive parenting attitudes and psychological wellbeing. Method: The cross-sectional study was conducted from August 2023 to February 2024 after approval from the ethics review board of King Edward Medical University, Lahore, Pakistan, and comprised stay-at-home mothers aged 20-65 years from the Punjab province. Data was collected using the Intensive Parenting Attitudes Questionnaire, the Guilt and Shame Experience Scale, and the Ryff’s Scale of Psychological Wellbeing. Data was analysed using SPSS 27. Results: Of the 200 mothers with mean age 42.5+/-9.0 years, 176(88%) from urban areas, 24(12%) from rural areas, 14(7%) had no formal education, 7(3.5%) had a postgraduate degree, and 192(96%) were married. Overall, psychological wellbeing of the mothers was predicted positively by fulfilment, and negatively by shame and guilt (p<0.001). Conclusion: Stay-at-home mothers endorsed intensive parenting attitudes, which, along with guilt and shame, predicted their psychological wellbeing. Key Words: Parenting, Guilt, Shame, Mental health, Mothers.